The Use of Image Media to Improve Student Learning Outcomes in Pancasila Education Lessons - Indah Saputri; Muh Ngali Zainal Makmun; Lutfi Fadilah; Majdy Kasheem (CV. Creative Tugu Pena, 2025)
This study aims to analyze the use of image media in improving student learning outcomes in Pancasila Education subjects in class IIA MI NU Metro. The main problem raised is the low student learning outcomes due to less varied learning methods and minimal use of media that are in accordance with student characteristics. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study were class IIA students consisting of 26 students. The results of the study showed that the use of image media made a real contribution to improving conceptual understanding, student activeness in learning, and higher learning motivation. Images that are relevant to the teaching material help students connect new knowledge with their concrete experiences. The main contribution of this study is to provide an empirical picture of the effectiveness of visual media in learning Pancasila Education at the elementary level, especially for students with concrete cognitive abilities. This study also shows the importance of the role of teachers in selecting and designing appropriate media so that the learning process becomes more meaningful and enjoyable.